COMMUNICATIVE MECHANISMS FOR OVERCOMING HUMAN ALIENATION IN CONDITIONS OF INFORMATIONAL UNCERTAINTY - Kovtun, Nataliia; Amma , Aleftina (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
In recent decades, the global information space has become an arena for the spread of post-truth, propaganda narratives, false and manipulative information, which has significantly undermined citizens’ trust not only in traditional media but also in electronic information resources. In such conditions, people are increasingly falling into a state of political, economic, and informational alienation, which in turn leads to a rise in social and political apathy. The aim of the article is to study the communicative mechanisms of overcoming alienation in a situation of global information uncertainty. Research methods. The article uses the methodology of system analysis, which allowed us to consider human alienation through the prism of its manifestation in various spheres of society (political, economic, legal, religious, informational, etc.) and hermeneutic analysis, which allowed us to reveal key approaches to understanding human alienation in a historical and philosophical retrospective. Research results and discussion. Within the framework of discussing the issue of overcoming alienation in the information society, various aspects of personal and social alienation of individuals were considered; the relationship between the destructive and constructive influence of the latest information technologies on the processes of human alienation was revealed; and various conceptual approaches to overcoming alienation in the context of the accelerated informatization of modern human existence were analyzed. Conclusions. It has been established that at the individual level of existence, the reduction of human alienation in conditions of informational uncertainty occurs through the following mechanisms: the actualization of love as active involvement with the Other; overcoming narcissism and selfishness in a person; developing modesty, objectivity, common sense, independence, responsibility, a high level of adaptability, and involvement in public, cultural, and political life. It has been substantiated that the levelling of alienation at the social level of communicative interaction provides mechanisms for the development of responsible elites, civil society, strengthening the capacity for social solidarity, achieving social harmony, promoting social dialogue, decentralisation, dismantling rigid systems of planning and grouping, etc. These mechanisms are directly related to the elimination of rigid social and informational control over individuals by state and commercial institutions.